A reflection on pandemic Covid-19 in Dean Koontz novel the Eyes of Darkness - Rumambo PANDIN, Moses Glorino; WIDJAYATI, Siti Eko (Opción)
The phenomenon of COVID-19 does not only exist in the current realities, but that reality has also been described in literary works such as the work of Dean Koontz. This study aims to highlight the attempts that the female character in the Novel encounters in her struggle against the patriarchal domination. The research method used is authentic realism approach with a content analysis by focusing on objectivity and reality, clarifying the text so that it can identify the elements in the text substantially by using the existing data and theories. The findings reveal that the Authentic Realism approach allows the researchers to see more clearly the contents of the main character in the Novel.